2008
DOI: 10.1111/j.1365-2109.2007.01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships in grey mullets (Mugilidae) in a Tunisian lagoon

Abstract: The Mugilidae family is an important fish group representing a major source for fisheries and aquaculture. In the south Mediterranean bank, no data are available on this fauna, except for some morphological studies on Tunisian samples. In this study, 16 allozymic loci were used to investigate the phylogenetic relationships within Tunisian mugilids. The results obtained from Hergla lagoon samples highlight five operational taxonomic unit corresponding to the well‐known species (Liza aurata, Liza ramada, Liza sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Moreover, RAPD analysis might be useful for systematic investigation at the level of species and subspecies (Bardakci and Skibinski, 1994), and more sensitive and technically easier to perform and produced results with low statistical error, whereas DNA fingerprinting detected greater genetic differentiation between Nile tilapia stains than other molecular techniques such as multilocus minisatellite marker (Naish et al, 1995). The results of this study are consistent with the findings reported by (Papasotiropoulos et al, 2001(Papasotiropoulos et al, , 2002(Papasotiropoulos et al, , 2007Blel et al, 2008;Semina et al, 2007), they applied several techniques for genetic analysis among Mugilidae family and reported that M. cephalus is the most distinct species compared with Liza genus. Also, the results confirmed that the amount of differences in genotype reflected the same amount of differences in phenotype between M. cephalus and L. ramada.…”
Section: Liza Ramadasupporting
confidence: 83%
“…Moreover, RAPD analysis might be useful for systematic investigation at the level of species and subspecies (Bardakci and Skibinski, 1994), and more sensitive and technically easier to perform and produced results with low statistical error, whereas DNA fingerprinting detected greater genetic differentiation between Nile tilapia stains than other molecular techniques such as multilocus minisatellite marker (Naish et al, 1995). The results of this study are consistent with the findings reported by (Papasotiropoulos et al, 2001(Papasotiropoulos et al, , 2002(Papasotiropoulos et al, , 2007Blel et al, 2008;Semina et al, 2007), they applied several techniques for genetic analysis among Mugilidae family and reported that M. cephalus is the most distinct species compared with Liza genus. Also, the results confirmed that the amount of differences in genotype reflected the same amount of differences in phenotype between M. cephalus and L. ramada.…”
Section: Liza Ramadasupporting
confidence: 83%
“…The second clade including Mugil cephalus. The results of this study are consistent with the findings reported by (Papasotiropoulos et al, 2001(Papasotiropoulos et al, , 2002(Papasotiropoulos et al, , 2007Blel et al, 2008;Semina et al, 2007), they applied several techniques for genetic analysis among Mugilidae family and reported that M. cephalus is the most distinct species compared with Liza genus The result of genetic similarity among Mullet species indicated highly expected success of interspecific hybridization between Liza aurata, Liza saline, and Liza ramada also the hybridization may be succeeded between Mugil cephalus and Liza group. The genetic similarity by RAPD marker can be used as a rapid method for predicting the specific hybridization between Mullet spp.…”
Section: Discussionsupporting
confidence: 91%
“…Phylogenetic relationships within the Mugilidae have largely been based on specimens collected within particular geographic regions, such as India (Menezes, 1992), East Asia (Lee et al, 1995, Liu et al, 2010, America (Fraga et al, 2007), and the Mediterranean (Autem and Bonhomme, 1980;Blel et al, 2008;Caldara et al, 1996;Erguden et al, 2010;Gornung et al, 2007;Imsiridou et al, 2007;Murgia et al, 2002;Papasotiropoulos et al, 2001Papasotiropoulos et al, , 2002Papasotiropoulos et al, , 2007Rossi et al, 1998aRossi et al, , 2004Semina et al, 2007;Turan et al, 2005). The above studies have generally demonstrated an early rapid divergence for the Mugil lineage and have led to a questioning of the monophyly of the genera Chelon and Liza (Aurelle et al 2008).…”
Section: Introductionmentioning
confidence: 99%